If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 6y = 56 Combine like terms: 8y + 6y = 14y 14y = 56 Solving 14y = 56 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '14'. y = 4 Simplifying y = 4
| (29/36)x+120=x | | 60x-13=72x-3-24x | | 103-2x=16x+21 | | 5x-15+2x-14=x-11 | | 5x-2x+12=35-4x-9 | | y=-(1+1)(1-3) | | 2g-8=10-4g | | X^2+7-9=0 | | 105*13/35*8/9 | | 5x-3.2=2x+2.8 | | 7x-91=2x-6 | | 32=17+x/2 | | 9x+10=3x+40 | | 48-2x=16x+24 | | F-2=3f+6 | | 5(x+3)+3(x-1)=-9 | | X/4+7=14 | | 21=(5x/6)+(3x/2) | | 2(x-4)+3(x+5)=2x | | 5.3q-1.9-4.6q=-0.3q-1.5 | | 2x-8+3x+18=2x | | 33/25*10/117*27/22 | | -2y+5x=-9 | | 62-9x=7x+18 | | x/3-26 | | 2x-5=57 | | x/2=48 | | x/4+x/3=7/4 | | 2f-7=43 | | x/6=15 | | x/2=46 | | 5c-11=19 |